The impact of economic crisis on regions dominated by motor vehicles industry (the case of Vysočina Region) - Šerý, Ondřej (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
The Czech economy has been significantly affected by the global economic crisis since the second half of 2008. The Czech economy is strongly dependant on the motor vehicles industry, the sector severely hit by the crisis. There are not only three major automobile companies in the Czech Republic (Škoda Auto Mladá Boleslav, TPCA Czech Kolín and Hyundai Motor Manufacturing Czech Nošovice), but there are also many subcontractors. The Vysočina Region, the model territory used in this article, has several such major companies. This fact had quite a significant impact on the economic situation in the Vysočina Region during the crisis. The paper also examines individual anti-crisis measures adopted by the largest subcontractor to the motor vehicle industry in the region, Bosch Diesel s.r.o. Jihlava.This paper was elaborated under the students’ support project at the Faculty of Science, “Strengthening and Improving Students Creative Work in the Fields of Mathematics, Physics and Earth Science “(KVAS-MPG). The project is funded by Masaryk University and it is aimed at supporting student projects at MU (MUNI/A/1060/2009)